Impact of Capital Flight on Economic Growth: Evidence from Nigeria (Lapai Journal of Economics, 2021)
This paper examines the impact of capital flight on economic growth in Nigeria within the context of the Autoregressive Distributed Lag (ARDL) estimation technique. The study utilizes annual data for the period 1981 to 2019, which was sourced from the Statistical Bulletin of the Central Bank of Nigeria (CBN) and World Bank's World Development Index (WDI) data on Nigeria. The result confirms the existence of cointegration and that capital flight has a negative impact on the economic growth of Nigeria. The study, therefore recommends that government should create a business-friendly environment by increasing its foreign reserve and reducing external indebtedness as well as invest heavily in basic infrastructure to attract FDI.